How We Know Early Hadīth Critics Did Matn Criticism and Why It's So Hard to Find - Brown, Jonathan (Islamic law and society, 2008)
Abstract Western scholars generally agree that early hadīth critics limited their authentication of hadīths to examining isnāds. The argument that these critics took the matn into account has relied on material of dubious reliability or on works produced after the formative period of the Sunni hadīth tradition. By providing examples of matn criticism from the 3rd/9th and 4th/10th centuries, I prove that Sunni hadīth critics did in fact engage in matn criticism; and I argue that these critics consciously manufactured the image of exclusive focus on the isnād in an effort to ward off attacks by rationalist opponents. By demonstrating a high correlation between the hadīths found in early books of transmitter criticism and those found in later books of forged hadīth with explicit matn criticism, I show that early critics engaged in matn criticism far more often than appears to have been the case, disguising this activity in the language of isnād criticism.